2006
DOI: 10.1364/ol.31.000181
|View full text |Cite
|
Sign up to set email alerts
|

Depth from diffracted rotation

Abstract: The accuracy of depth estimation based on defocus effects has been essentially limited by the depth of field of the imaging system. We show that depth estimation can be improved significantly relative to classical methods by exploiting three-dimensional diffraction effects. We formulate the problem by using information theory analysis and present, to the best of our knowledge, a new paradigm for depth estimation based on spatially rotating point-spread functions (PSFs). Such PSFs are fundamentally more sensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
127
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 193 publications
(130 citation statements)
references
References 16 publications
2
127
0
1
Order By: Relevance
“…A phase mask that minimizes the Fisher information results in a PSF that is insensitive to defocus, thus granting the optical system extended depth of field. In contrast, in [21] the authors designed a phase-amplitude mask that results in a rotating PSF that yields a high Fisher information with respect to defocus. This allowed them to estimate the depth of a two-dimensional thin object from the rotation angle of the PSF via a deconvolution process.…”
Section: Analysis Of the Performance Of The Lfm Based On Fisher Informentioning
confidence: 99%
“…A phase mask that minimizes the Fisher information results in a PSF that is insensitive to defocus, thus granting the optical system extended depth of field. In contrast, in [21] the authors designed a phase-amplitude mask that results in a rotating PSF that yields a high Fisher information with respect to defocus. This allowed them to estimate the depth of a two-dimensional thin object from the rotation angle of the PSF via a deconvolution process.…”
Section: Analysis Of the Performance Of The Lfm Based On Fisher Informentioning
confidence: 99%
“…1(a) and 1(b), respectively. The DH-PSF enhances the Fisher information for axial localization and can be used for 3D imaging applications like localization based microscopy [22], particle tracking [22][23][24], super-resolution imaging [12], depth ranging [25], profilometry and imaging optical tweezers [26]. The DH-PSF allows 3D localization of multiple sparse particles in a single image with high localization precision and longer depthof-field than other 3D localization methods [18], making it attractive for tracking and superresolution imaging.…”
Section: An Information Optimized Dh-psf Designmentioning
confidence: 99%
“…1B Inset). This method is based on earlier work that showed that rotating intensity DH-PSF distributions could be formed by taking superpositions of G-Laguerre (GL) modes that form a cloud along a line in the GL modal plane (23)(24)(25). The DH-PSF has been used to localize photon-unlimited point scatterers inside the volume of a glass slide, and to track moving fluorescent microspheres (26).…”
mentioning
confidence: 99%